Frequent Small Distractions with a Magnetically Controlled Growing Rod for Early-Onset Scoliosis and Avoidance of the Law of Diminishing Returns. (December 2016) - Cheung, Jason Pui Yin; Bow, Cora; Samartzis, Dino; Kwan, Kenny; Cheung, Kenneth Man Chee
Purpose: To assess the effect of frequent small distractions with a magnetically controlled growing rod (MCGR) on spinal length gain and achieved distraction length in children with early-onset scoliosis (EOS), and to determine whether the law of diminishing returns applies to this group of patients with MCGR. Methods: A consecutive series of 3 males and 4 females with EOS who underwent MCGR implantation at a mean age of 10.2 years and were followed up for a mean of 3.8 years were reviewed. Distraction was aimed at 2 mm monthly. The coronal Cobb angle, T1-S1 length gain, and achieved distraction length were measured at 6-monthly intervals. Results: The mean total number of distractions was 31. Four of the patients had problems that may have affected distractions. The mean coronal Cobb angle improved post-operatively and was maintained throughout the follow-up period. The mean T1-S1 length gain and achieved distraction length varied over the follow-up period and did not diminish with repeated lengthening. Conclusions: Frequent small distractions with the MCGR for EOS enable T1-S1 and achieved distraction length gain without significant reduction in gain after repeated lengthening.